Power Loss Reduction and Voltage Improvement by Relocation of Distribution Transformers: A Comprehensive Case Study - Sadiq, Emad Hussen; Antar, Rakan Khalil (Journal of Engineering and Technological Sciences, 2026)
Due to the rapid growth and expansion of the electricity industry, power systems worldwide are facing significant challenges that demand immediate attention to manage the increasing load. Many power system operators are struggling with insufficient power generation capacity. To mitigate the effects of limited power availability, reducing power losses and improving voltage profiles have become essential components of modern energy management. One effective approach to achieving these objectives in distribution networks is optimizing the placement of distribution transformers. In this study, the Electrical Transient Analyzer Program (ETAP) software is employed to evaluate selected transformer locations with respect to both power loss reduction and voltage drop performance. The findings indicate a significant reduction in power losses accompanied by a notable enhancement in the voltage profile.